Malignant retroperitoneal schwannoma in a young adult: rapid recurrence, metastasis, and treatment reflections—a case report - Zhao, Zeming; Fan, Shaoqing; Yu, Donghao; Wang, Guiying (Frontiers in Oncology, 2025)
Retroperitoneal schwannoma, a rare mesenchymal-derived tumor originating from the retroperitoneum. Malignant retroperitoneal schwannoma carries a dismal prognosis. We present a case of a 19-year-old male who presented with left abdominal pain. Imaging examination revealed a large retroperitoneal mass (16×12×9 cm) in the left upper quadrant. Pathological examination following surgical resection confirmed the diagnosis of malignant schwannoma, with a notably high Ki-67 proliferation index of 50%. Despite radical resection, the tumor recurred with metastases to the ilium and sacrum within two years postoperatively. The patient ultimately discontinued treatment due to disease progression. This case underscores the aggressive nature of retroperitoneal malignant schwannoma, characterized by rapid local recurrence, distant metastasis, and resistance to surgical cure. These findings emphasize the urgent need for effective postoperative adjuvant therapies to improve outcomes in this highly malignant entity.